Case report: Somatic mutations in microtubule dynamics-associated genes in patients with WNT-medulloblastoma tumors - Skitchenko, Rostislav; Dinikina, Yulia; Smirnov, Sergey; Krapivin, Mikhail; Smirnova, Anna; Morgacheva, Daria; Artomov, Mykyta (Frontiers in Oncology, 2023)
Medulloblastoma (MB) is the most common pediatric brain tumor which accounts for about 20% of all pediatric brain tumors and 63% of intracranial embryonal tumors. MB is considered to arise from precursor cell populations present during an early brain development. Most cases (~70%) of MB occur at the age of 1–4 and 5–9, but are also infrequently found in adults. Total annual frequency of pediatric tumors is about 5 cases per 1 million children. WNT-subtype of MB is characterized by a high probability of remission, with a long-term survival rate of about 90%. However, in some rare cases there may be increased metastatic activity, which dramatically reduces the likelihood of a favorable outcome. Here we report two cases of MB with a histological pattern consistent with desmoplastic/nodular (DP) and classic MB, and genetically classified as WNT-MB. Both cases showed putative causal somatic protein truncating mutations identified in microtubule-associated genes: ARID2, TUBB4A, and ANK3.